Kesejahteraan Subjektif dan Altruisme Memprediksi Kesadaran Lingkungan: Subjective Well-Being and Altruism Predict Environmental Awareness - Riki Adimas Fitrianto; Lely Ika Mariyati (Academia Open, 2025)
General Background: The growth of eco-tourism development requires psychological insights to support sustainable environmental management at the community level. Specific Background: Gunung Petung Village, particularly the Sumber Nyonya Waterfall area, represents a developing rural tourism destination where residents’ environmental awareness plays a central role. Knowledge Gap: Limited empirical studies examine how subjective well-being and altruism jointly relate to environmental awareness within local tourism development contexts. Aims: This study investigates the role of subjective well-being and altruism in shaping environmental awareness among village residents. Results: Using a quantitative approach with 172 participants selected from a population of 336 residents, findings indicate that subjective well-being (r=0.313) and altruism (r=0.319) are positively correlated with environmental awareness, and jointly show significant statistical contribution (F=16.087, p=0.001). Novelty: The study integrates psychological well-being and prosocial orientation within a rural eco-tourism setting. Implications: The findings provide theoretical insight into psychological determinants of environmental consciousness and inform community-based strategies for sustainable tourism development. Keywords: Environmental Awareness, Subjective Well-Being, Altruism. Sustainable Tourism, Community Psychology Key Findings Highlights: Subjective life satisfaction correlates positively with ecological consciousness. Prosocial orientation is associated with stronger community-based conservation attitudes. Psychological factors jointly contribute to sustainable rural tourism development.